2016
DOI: 10.1096/fj.201600388r
|View full text |Cite|
|
Sign up to set email alerts
|

The epithelial–mesenchymal transition (EMT) is regulated by oncoviruses in cancer

Abstract: The epithelial-mesenchymal transition (EMT), defined as transdifferentiation of epithelial cells into mesenchymal cells, is critical for embryonic development, wound healing, tissue regeneration, organ fibrosis, and cancer progression. Recently, the role of EMT in carcinogenesis has attracted much attention. Oncoviruses, including human papillomaviruses (HPVs), Epstein-Barr virus (EBV), and hepatitis B and C viruses (HBVs, HCVs), are known to be involved in the etiology of cancer and have been found to play im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 121 publications
(154 reference statements)
0
44
0
Order By: Relevance
“…While HPV infections are eradicated by the immune system, persistent chronic infections associated with high expression levels of E6/E7 (viral oncogenes) as well as accretion of cellular mutations may cause alterations in TP53 and RB expressions, which are known as tumor suppressor genes [6]. Additionally, it has been reported that high-risk HPVs (E5 and E6/E7) oncoproteins, can enhance cancer progression of human carcinomas via the initiation of the epithelial-mesenchymal transition (EMT) which is a hallmark of cancer metastasis [7][8][9]. On the other hand, it is important to note that HPVs transmissions may be enhanced by the presence of rough or macerated epithelial surfaces [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While HPV infections are eradicated by the immune system, persistent chronic infections associated with high expression levels of E6/E7 (viral oncogenes) as well as accretion of cellular mutations may cause alterations in TP53 and RB expressions, which are known as tumor suppressor genes [6]. Additionally, it has been reported that high-risk HPVs (E5 and E6/E7) oncoproteins, can enhance cancer progression of human carcinomas via the initiation of the epithelial-mesenchymal transition (EMT) which is a hallmark of cancer metastasis [7][8][9]. On the other hand, it is important to note that HPVs transmissions may be enhanced by the presence of rough or macerated epithelial surfaces [10].…”
mentioning
confidence: 99%
“…LMP-1 variants are divided into 7 core groups including B95-8, Alaskan, China 1, China 2, Med+ , Med− , and NC [18,23,24]. LMP1 can stimulate several signaling pathways especially those involved in the induction of EMT such as NF-κB, PI3K/Akt, and MAPK [7]. The other EBV onco-protein, LMP2A [25] regulates the invasive/migratory ability and stimulates changes in EMT-like cellular biomarkers [26] by targeting the rapamycin (mTOR) pathway [22].…”
mentioning
confidence: 99%
“…Microbial pathogens that induce chronic inflammation can promote EMT (14). Bacteria such as Helicobacter pylori, Escherichia coli, and Klebsiella pneumoniae and viruses such as Epstein-Barr virus (EBV) and hepatitis C virus (HCV) are known to induce EMT (15,16). We hypothesized that persistent TGEV infection would have the same effect on cells and that after EMT, cells would be more susceptible to bacterial pathogens.…”
mentioning
confidence: 99%
“…1Y3 Recent investigations suggested that HPV pushes cancer progression through EMT event. 24,25 To test if HPVoncoproteins affect the YB-1YSnail-EMTaxis, we knocked down HPV18 E6 from Hela cells to observe the change of mRNA and protein levels of YB-1 and Snail. The results showed that E6 knockdown decreased YB-1 and Snail expressions, which indicated that E6 could control the YB-1YSnail-EMTaxis.…”
Section: Discussionmentioning
confidence: 99%